Hubungan Kampanye New Normal dengan Tingkat Kesadaran Mahasiswa - Khansa Arifah Rahmah; Zulfebriges (UNISBA Press, 2022)
Abstract. A new outbreak that attacked humans was found in Wuhan, China, China in December 2019. This outbreak had an impact on inflammation in the respiratory tract and was known as Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-COV2) or people called it COVID. -19 (Coronavirus Disease-2019). The formulation of the problem in this study is